The historical relation between clause-final negation markers and phasal polarity expressions in Sub-Saharan Africa - (:unkn) unknown (My University, 2021)
Clause-final negation markers (CFNMs), although typologically rare, can be found in a very wide range of languages of Sub-Saharan Africa. Given that CFNMs tend to occupy the same constructional slot as phasal polarity expressions (PPEs) and that strong semantic and often also formal links are known to exist between PPEs and negation, default CFNMs may be expected to often develop out of PPEs. However, this expectation is not borne out by the data available on the development of default CFNMs in the languages of Sub-Saharan Africa. The paper discusses a number of cases from Mande languages where CFNMs may be argued to be historically related to PPEs. In line with the general rarity of the change from a PPE to a default CFNM, when evolving into negation markers PPEs tend to maintain the phasal element of their semantics or become restricted to certain TAM constructions. In those rare cases where PPEs may be argued to have evolved into default CFNMs, this evolution is not direct and necessarily proceeds through the addition (or foregrounding) of a free-choice indefinite semantic component (such as 'not yet' > 'not ever yet, not on any occasion yet') and the development of the implicature of an intersubjective operator processing hearer-sided expectations and presuppositions (such as 'not ever yet, not on any occasion yet' > 'not at all, really not').
Keywords: African Research